Youth Participation in Agriculture in the Nkonkobe District Municipality, South Africa - Priviledge Cheteni (Journal of Human Ecology, 2016)
In this paper, a binary logistic model was used to analyse the determinants of youth participation in agriculture in the Nkonkobe Municipality in South Africa. A total of 140 youth were purposively selected for the study to complete a survey. The results show that the variables; youth programmes, programme availability, and resources were statistically significant in explaining the factors that affect youth participation in agricultural activities. Based on the study findings, it is recommended that in order to influence youth participation, they should be provided with youth programmes and resources.
Keywords: Q; 330; Binary model; New Growth Plan; Perception; Rural Development; Youth Participation